Group Cohesion and Application of Best Horticultural Farming Practices among Farmer Groups in Meru County, Kenya - Raphael Mwiti Gikunda; David E. Lawver (Journal of International Agricultural and Extension Education, 2019)
This study illuminates the power of farmer groups as avenues for mobilizing farmers around a common objective, thus adds to the knowledge base of extension education. A quantitative approach involving the use of a correlational research design was adopted to describe the association between group cohesion and application of BHFP. The target population was 1950 farmers from 35 farmer groups. Stratified random sampling was used to select a sample of 112 farmers from the population. Data were collected by use of a self-administered structured questionnaire developed by the researcher. Statistical Package for Social Sciences (SPSS) was used for data analysis, which involved both descriptive and inferential statistics. According to the results, most (70.5%) of the farmers felt that the level of cohesion among members of their groups was very high. Pearson correlation test indicated that there was a weak negative significant correlation between group size and level of cohesion (r = -.27, N =112, p <.05) and a positive moderate significant correlation between group cohesion and application of BHFP (r =.39, N =112, p <.05). The level of application of BHFP was high with the majority of the farmers (75.9%) scoring between 71 and 75 out of 75 points. It was concluded that group cohesion is related to the application of BHFP. However, there is a need for the group managers to limit the group sizes to maintain a high level of cohesion, and sustain a conducive environment that triggers a team climate that supports the application of BHFP.
Keywords: Best horticultural practices; farmer groups; cohesion; group size